(3GOGQI GdehGQO GdHTQjI (B:s (3eONd GSJQGJjLj eJcGed (B/s - (3GdWGFj, jhSa MLjes; (3GdYHGOj, gGTe ahRj s; (3GdaVd, eDjO YHO GdMSjf s ((3YeGf(B: s (3OGQ GdhQGb ddfTQ hGdJhRjY(B, s, 2006)
(3GHYGO hXjaI GOGQI GdehGQO GdHTQjI(B, (3JNWjW GdehGQO GdHTQjI h cPG GdJhXja aj GdefTBJ h JfejI GdehGQO GdHTQjI(B, (3JYhjV GdehGQO GdHTQjI(B, (3UjGfI GdehGQO GdHTQjI h GdeMGaXI YdjgG(B, (3GOGQI YdGbGJ GdehXajf h GNjQ bVGjG NGUI aj GOGQI GdehdQO GdHTQjI(B.s
Keywords: (3GOGQI GdGYeGds; (3GOGQIGdGaQGOs; (3GdehGQO GdHTQjIs